Minerals Associated with Biofilms Occurring on Exposed Rock in a Granitic Underground Research Laboratory - Brown, D. Ann (1994)
The concept of disposal of nuclear fuel waste in crystalline rock requires the effects of microbial action to be investigated. The Underground Research Laboratory excavated in a pluton of the Canadian Shield provides a unique opportunity to study these effects. Three biofilms kept moist by seepage through fractures in granitic rock faces of the Underground Research Laboratory have been examined. The biofilms contained a variety of gram-negative and gram-positive morphotypes held together by an organic extracellular matrix. Nutrient levels in the groundwater were low, but energy-dispersive X-ray spectroscopy has shown biogeochemical immobilization of several elements in the biofilms; some of these elements were concentrated from extremely dilute environmental concentrations, and all elements were chemically complexed together to form amorphous or crystalline fine-grained minerals. These were seen by transmission electron microscopy to be both associated with the surfaces of the bacteria and scattered throughout the extracellular matrix, suggesting their de novo development through bacterial surface-mediated nucleation. The biofilm consortia are thought to concentrate elements both by passive sorption and by energy metabolism. By Mössbauer spectroscopy and X-ray diffraction, one of the biofilms showed that iron was both oxidized and precipitated as ferrihydrite or hematite aerobically and reduced and precipitated as siderite anaerobically. We believe that some Archean banded-iron formations could have been formed in a manner similar to this, as it would explain the deposition of hematite and siderite in close proximity. This biogeochemical development of minerals may also affect the transport of material in waste disposal sites.